PENGARUH INTENSITAS PENGGUNAAN HANDPHONE TERHADAP PERILAKU SISWA KELAS VIII C DI SMP MUHAMMADIYAH 7 SURAKARTA TAHUN AJARAN 2022/2023 - Yudhaswari, Sekar Wening Latifa; Syamsuddin, S; Praptiningsih, P (Al’ulum Jurnal Pendidikan Islam, 2024)
Currently, the millennial generation, a generation that is proficient in technology, is infatuated with various types of cellphones. This study aims to determine the effect of the intensity of mobile phone use on student behavior. This type of research is quantitative research with research subjects at SMP Muhammadiyah 7 Surakarta. The independent variable (Variable X) in this study is the intensity of mobile phone use, while the dependent variable (Variable Y) is student behavior. The research population consisted of 4 classes and a sample of 1 class, namely 30 people. In collecting data, researchers used an instrument in the form of a questionnaire consisting of 20 item questions, testing the validity of the research instrument using the Aiken Validity Test and testing its reliability using the Cronbach Alpha Test. The scoring of question items in the questionnaire uses a Likert scale of 1-4. The results showed that there was an influence between the intensity of mobile phone use on student behavior at SMP Muhammadiyah 7 Surakarta. Judging from the test results using the product moment, the r count value is 0.482 and the r table value is 0.361. With the testing criteria r count > r table. Then H0 is rejected so that there is a significant influence between the intensity of mobile phone use on student behavior at SMP Muhammadiyah 7 Surakarta. Then in the calculation of the coefficient of determination it is known that the value of r square is 0.482, namely the influence of the intensity of using mobile phones on student behavior at SMP Muhammadiyah 7 Surakarta by 23.21%. This means that the influence of the intensity of mobile phone use on student behavior is in the medium category.